2005
DOI: 10.1017/s0952836905006576
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of food resources by badgers ( Meles meles ) in the Swiss Jura Mountains

Abstract: In our study three badger Meles meles populations separated by only a few km but subjected to different environmental conditions were compared. Differences are especially marked for climatic factors, the three areas being located at different altitudes, and for intensivity of soil use by people. The diet of the three populations was significantly different, with one or two dominant items in each area: mammals and cereals in the mountain, maize in the mid-mountain and in the lowland areas. In the most intensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 36 publications
3
20
0
2
Order By: Relevance
“…Furthermore, den-watching and night-lighting were used to assess social organization and population density. We discuss our findings with respect to published results on the feeding habits of badgers in the area (Weber and Aubry 1994;Fischer et al 2005) as well as in the context of the wide range of spatio-temporal patterns, social systems and densities observed throughout Europe in this mustelid.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Furthermore, den-watching and night-lighting were used to assess social organization and population density. We discuss our findings with respect to published results on the feeding habits of badgers in the area (Weber and Aubry 1994;Fischer et al 2005) as well as in the context of the wide range of spatio-temporal patterns, social systems and densities observed throughout Europe in this mustelid.…”
Section: Introductionsupporting
confidence: 53%
“…However, whereas oligochaetes were indeed the main prey of badgers during low phases of the multiannual water vole (Arvicola terrestris shermann) population cycle (Saucy 1988), rodents constituted the bulk of badger diet during periods of high vole densities (Weber and Aubry 1994). In between these phases of the cycle, a scenario which characterized the years during which our study was conducted (1993)(1994)(1995)(1996), Fischer et al (2005) showed that oligochaetes only represented about 11% of badgers' diet, and that badgers fed seasonally on a large variety of animal (small mammals, insects, earthworms) and plant items (fruits, cereals). In accordance with our habitat use data, cereals were important components of summer and autumnal diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Localities across Eurasia from which data was obtained from publications [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. We used the relative frequency of occurrence to access the diet of badgers.…”
Section: Figurementioning
confidence: 99%
“…Here, we take the badgers across the Eurasia as a single species. The feeding ecology of badger has been the subject of numerous studies at many localities throuth out its distribution range, such as in England [11], Italy [12][13][14][15][16][17][18][19][20], Hungary [21], Ireland [22], Poland [23], Japan [24], Mongolia [25], Scotland [26], Spain [27][28][29] and Swiss [30]. Some researchers argued that badger is an earthworm specialist predator [26,31]; while other studies indicated that the badger is a generalist predator that uses resources according to its availability [19,27,29].…”
mentioning
confidence: 99%